Cigarette Smoking Preferentially Affects Intracranial Vessels in Young Males: A Propensity-Score Matching Analysis - Yunsun Song; Dongwhane Lee; Dae Chul Suh; Joong-goo Kim; Jae Kyun Kim; Minkyu Han; Hairi Liu; Lingbo Zhao; Eun Hye Kim; Sung Chul Jung; Dong-geun Lee; Hyun Jung Koo; et al. (Neurointervention, 2019)
Purpose Cigarette smoking (CS) is one of the major risk factors of cerebral atherosclerotic disease, however, its level of contribution to extracranial and intracranial atherosclerotic stenosis (ECAS and ICAS) was not fully revealed yet. The purpose of our study was to assess the association of CS to cerebral atherosclerosis along with other risk factors. Materials and Methods All consecutive patients who were angiographically confirmed with severe symptomatic cerebral atherosclerotic disease between January 2002 and December 2012 were included in this study. Multivariate logistic regression analyses were performed to identify risk factors for ECAS and ICAS. Thereafter, CS group were compared to non-CS group in the entire study population and in a propensity-score matched population with two different age-subgroups. Results Of 1709 enrolled patients, 794 (46.5%) had extracranial (EC) lesions and the other 915 (53.5%) had intracranial (IC) lesions. CS group had more EC lesions (55.8% vs. 35.3%, P<0.001) whereas young age group (<50 years) had more IC lesion (84.5% vs. 47.6%, P<0.001). In multivariate analysis, seven variables including CS, male, old age, coronary heart disease, higher erythrocyte sedimentation rate, multiple lesions, and anterior lesion were independently associated with ECAS. In the propensity-score matched CS group had significant more EC lesion compared to non-CS group (65.7% vs. 47.9%) only in the old age subgroup. Conclusion In contrast to a significant association between CS and severe symptomatic ECAS shown in old population, young patients did not show this association and showed relatively higher preference of ICAS.